IPMN Involving the Main Pancreatic Duct. Issue 5 (May 2015) - Marchegiani, Giovanni; Mino-Kenudson, Mari; Sahora, Klaus; Morales-Oyarvide, Vicente; Thayer, Sarah; Ferrone, Cristina; Warshaw, Andrew L.; Lillemoe, Keith D.; Fernández-del Castillo, Carlos
<x xml:space="preserve">Abstract</x> Objectives: To describe the characteristics of intraductal papillary mucinous neoplasms (IPMNs) with predominant involvement of the main pancreatic duct (MPD), analyzing predictors for survival and recurrence. Background: IPMNs involving the MPD harbor a high likelihood of malignancy and different biological features. The appropriateness of including cases with minimal noncircumferential MPD involvement has been challenged because these show clinicopathological features that are similar to branch duct IPMN. Accordingly, their exclusion has led to a redefinition of MPD IPMN (MD-IPMN). Methods: Retrospective review of resected MD-IPMN from 1990 to 2013. All slides were reviewed by a single pancreatic pathologist and classified on the basis of epithelial type and invasive component. Results: A total of 223 patients underwent resection for IPMN involving the MPD. Of these, 50 were excluded because of minimal MPD involvement. Among the 173 patients analyzed, median age was 68 years and 55% were males. Predominant epithelial phenotype was intestinal (50%). Forty-eight patients (28%) had low- or intermediate-grade dysplasia, whereas 125 (72%) had either high-grade dysplasia (33%) or invasive carcinoma (39%). Of the 67 invasive IPMNs, 39 were tubular carcinomas (58%) and invasion was minimal (<5 mm) in 28 (42%). The 5-year overall survival rate was 69% and the disease-specific survival rate was 83%. The estimated recurrence rate at 10 years was 25%. Size and type of the invasive component, lymph node positivity, and a positive resection margin were predictors for both survival and recurrence (P < 0.05). Conclusions: MD-IPMN is mainly intestinal-type and malignant. After resection, it has a very favorable prognosis, especially in the absence of macroscopic invasive carcinoma.